Effect of Task Presentation on the Performance of Crowd Workers — A Cognitive Study - Sampath, Harini; Rajeshuni, Rajeev; Indurkhya, Bipin; Karanam, Saraschandra; Dasgupta, Koustuv (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
We present our ongoing research on improving the task presentation using cognitively inspired features to optimize the performance of crowd workers. For the task of extracting text from scanned images, we generated three task-presentation designs by modifying two features of the task - visual saliency of target ﬁelds and working memory requirements. Our experiments conducted on Amazon Mechanical Turk (AMT) indicate that modifying visual saliency results in better performance.